Analysis of RC columns strengthened with ultra-high performance fiber reinforced concrete jackets under eccentric loading. (1st October 2020) - Sakr, Mohammed A.; El Korany, Tamer M.; Osama, Bothaina
Highlights: FE modeling of jacketed columns captured the experimental response reasonably well. Using adequate number of dowels led to a monolithic behavior of jacketed columns. An analytical model was proposed to draw the interaction envelop of jacketed columns. Abstract: This paper describes the development of finite-element (FE) and analytical models for investigating the behavior of reinforced concrete (RC) columns strengthened with UHPFRC jackets under axial or eccentric loading. The main goal of both types of models is to produce load-moment ( N - M ) interaction envelope for RC columns strengthened with UHPFRC jackets. In the FE model, a methodology to implement bond-slip model between core concrete-to-jacket concrete is presented. The interface is implemented using connector elements. The FE results were verified versus experimental results of other researches, showing high accuracy in relation to load-deformation, ultimate load capacity, and failure modes. Using the verified FE model, a parametric study on strengthened columns with UHPFRC jackets is carried out. Several parameters, including interfacial shear strength, UHPFRC jackets' thickness and number of dowels, are investigated. The results show that a monolithic behavior of strengthened columns can be attained by increasing the core surface texture, decreasing the jackets' thicknesses, and using adequate number of dowels. A new analytical model is proposed to generate the load-moment ( N-M ) interaction envelope of strengthened columns with UHPFRC jackets. A comparison between proposed analytical model and FE results in addition to experimental data available in the literature confirmed the accuracy and validity of the proposed analytical model.